Guest Editors' Introduction: The Challenges and Prospects of Deliberative Democracy for Corporate Sustainability and Responsibility. Issue 1 (January 2023) - Gilbert, Dirk Ulrich; Rasche, Andreas; Schormair, Maximilian J. L.; Singer, Abraham
Abstract : This introduction argues that the use of the concept of deliberative democracy in corporate social responsibility (CSR) research needs to be theoretically extended. We review three developments that have recently occurred in deliberative democracy theory within political science and philosophy: 1) the conceptualization of deliberative systems (macro level), 2) the considerations of mini-publics (micro level), and 3) the role of online deliberation. We discuss the challenges and prospects that incorporating these three developments into future CSR-related research creates. We thereby also introduce the articles in this special issue and show how they connect to each of the three developments. On the basis of this discussion, we outline the contours for a more general program of distributed deliberative CSR that enables CSR scholars to incorporate an updated understanding of deliberative democracy theory into their future work.